Two new species of Erica (Ericaceae) from the Langeberg, Western Cape, South Africa - R. C. Turner; E. G. H. Oliver (Bothalia: African Biodiversity & Conservation, 2006)
Two new species of the genus Erica L. from the north-facing slopes of the Langeberg are described— E turneri,  known only from the type locality on Zuurbraak Mountain and E. euryphylla,  occurring on the same mountain slope, as well as on the middle north-facing slopes   of Hermitage Peak near Misty Point in the Marloth Nature Reserve above Swellendam.